Sediment Recycling and the Evolution of Analog Orogenic Wedges. Issue 2 (7th February 2022) - Reitano, R.; Faccenna, C.; Funiciello, F.; Corbi, F.; Sternai, P.; Willett, S. D.; Sembroni, A.; Lanari, R.
Abstract: In convergent systems, the interplay between tectonics, erosion, and sedimentation controls the orogenic evolution. The nature of the interactions between these factors is still elusive due to the complex feedbacks that operate across different temporal and spatial scales. Here, we investigate these feedbacks with analog models of landscape evolution designed to account for both tectonic forcing and surface processes, using a water‐saturated granular material that allows to simulate contemporary brittle deformation and surface processes. The deformation is imposed by the movement of a rigid backstop, and surface processes are triggered by simulated rainfall and runoff. We vary the convergence velocity, rainfall rate, and basal angle of the box, testing how different boundary conditions affect the balance between tectonics and surface processes. We measure the competition between input fluxes (tectonics) and output fluxes (erosion) of material, showing how sedimentation strongly affects the balance between these fluxes. The results suggest that the experimental equilibrium between tectonics and erosion can be achieved, in the analog models, only for low convergence rates (about 10 mm hr −1 ) and/or for high basal angle (>2°, limited sedimentation). If the foreland is overfilled with sediments and/or if convergence velocity is higher, channels decrease their erosional efficiency, moving the dynamic equilibrium between tectonics and erosion toward the former. Plain Language Summary: Laboratory models are extremely useful in studying the interaction between processes that build (i.e., tectonics) and processes that carve and shape orogens (i.e., surface processes). We use a rectangular plexiglass box filled with an analog material made of granular materials (silica powder, glass microbeads, and PVC powder) to simulate the building of an accretionary wedge. Surface processes are triggered by a rainfall system above the models, made by commercial sprinklers. To study the interaction between tectonics and surface processes, we change the boundary conditions such as convergence velocity (i.e., the building of the orogenic wedge), and the basal slope (i.e., the inclination of the box toward the foreland). We noticed that the slower the convergence velocity, the higher is the possibility of surface processes adjusting to the tectonic forcing. The capability to remove sediments in front of the accretionary wedge also allows for a stronger response of surface processes to the imposed tectonic forcing. Key Points: Balance between tectonics and surface processes in analog accretionary wedges, using water‐saturated granular materials Effect of sedimentation in tuning the balance between tectonics and erosion Tectonics‐surface processes equilibrium for low analog convergence rates and/or high basal angles (lower sedimentation)